Vitamin D receptor-modulated Hsp70/AT1 expression may protect the kidneys of SHRs at the structural and functional levels - García, Isabel Mercedes (2013)
Background: From hypertension studies, have been well characterized low levels of vitamin D linked to the renin-angiotensin system exaltation as oxidative stress. The heat shock protein 70 (Hsp70) chaperone regulates a diverse set of signaling pathways for cellular oxidative stress responses. In addition, Hsp70 has been shown to protect against Angiotensin II-induced hypertension and exert a cytoprotective effect by down-regulation of Nox4. Aims: Here, we evaluated whether vitamin D receptor (VDR) associated with Hsp70/ AT1 expression may be involved in the mechanism by which paricalcitol exerts renal protection in spontaneously hypertensive rats (SHR). Methods: One-month-old female SRH were treated with vehicle, paricalcitol, enalapril, or combination of both for 4 months. The following were determined: blood pressure; biochemical parameters; fibrosis; apoptosis; mitochondrial morphology; VDR, AT1 receptor, and Hsp70 expression in renal cortex. Results: Blood pressure was markedly reduced by enalapril or combination but not by paricalcitol alone. However, VDR activation and/or enalapril prevented fibrosis (%), the number of TUNEL-positive apoptotic cells (), mitochondrial damage and NADPH oxidase activity, in SHR. Additionally, high AT1 receptor as low Hsp70 expression (immunohistochemical/ immunofluorescence studies) were reverted in renal cortexes from SHR paricalcitol and/or enalapril-treated animals, and these changes were most marked in the combination therapy group. Finally, all parameters recovery, were consistent with an improvement in VDR expression. Conclusions: These data suggest that Hsp70/ AT1 modulated by VDR are involved in the mechanism by which paricalcitol exerts renal protection in SHR. Also, the effect of combining paricalcitol and enalapril on cytoprotection suggest a compensatory/ additive feedback system.